Settling our differences: demonstration of the development of Derrida's system (1954-1967) - Galetti, Dino (My University, 2012)
In 1990, Derrida added an introduction to his earliest long work, his student mémoire of 1954, which explained that he found in that work a “law” that had continued to impose itself across his oeuvre. This dissertation investigates selected works of the early Derrida, from that first student work of 1954 up to segments of Of Grammology, to demonstrate how Derrida’s “law” developed at least as far as his early system in 1967, as a basis for approach to Derrida’s overall oeuvre.
A dissertation submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, for the degree of Doctor of Philosophy
Keywords: Derrida, Jacques; Difference (Philosophy)--History--20th century